Simplify 2^(x + 3y)*4^(x - y)/sqrt(2*4)

### 1 Answer | Add Yours

The expression `(2^(x + 3y)*4^(x - y))/sqrt(2*4)` has to be simplified.

`(2^(x + 3y)*4^(x - y))/sqrt(2*4)`

= `(2^(x + 3y)*4^(x - y))/8^(1/2)`

= `(2^(x + 3y)*4^(x - y))/2^(3/2)`

= `(2^(x + 3y)*2^(2x - 2y))/2^(3/2)`

use the property `a^x/a^y = a^(x - y)` and `a^x*a^y = a^(x + y)`

= `2^(x + 3y + 2x - 2y - 3/2)`

= `2^(3x + y - 3/2)`

**The simplified form of **` (2^(x + 3y)*4^(x - y))/sqrt(2*4) = 2^(3x + y - 3/2)`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes